Bir II. Alman İmparatorluğu Projesi: Kaiser Wilhelm Anıtı’ndan Alman Çeşmesi’ne - Göğüş, Ceren (Fen Bilimleri Enstitüsü, 2015)
2. Alman İmparatorluğu Kayzeri II. Wilhelm 1898 yılında Osmanlı topraklarına yaptığı geziden sonra gördüğü ilgi ve sevginin de etkisiyle dönemin sultanı II. Abdülhamid ve İstanbul halkına bir çeşme hediye etmeye karar vermiştir. İstanbul’un tarihi yönden en önemli merkezlerinden biri olan Sultanahmet Meydanı’nda yapılmasına karar verilen çeşme 1901 yılında tamamlanmış ve görkemli bir devlet töreni ile açılmıştır. Çeşme ilk bakışta, onu çevresindeki diğer yapılardan ayıran mimari özelliklere sahiptir ama tasarımı hakkında bir araştırma aslında Neo-Bizans prensiplerini tekrarlayan tasarımı ile en azından bulunduğu meydan, Roma ve Bizans döneminin Hipodromu ile ilişki kurduğunu gösterir. Gene de Alman Çeşmesi’nin inşası Alman güdümlü olarak gerçekleşmiştir. Çeşmenin biçimlenişi Alman kültürünün bir ürünüdür. Bu hem taşıdığı sembolizmin ve anıtsallığının Osmanlı kültürü tarafından bilinen ve kabul edilen parametreler içinden değil Alman 19. yüzyılının anıt kavramından gelmesinden, hem de Alman hükümdarının 19. yüzyıl Avrupa kültürü içinde doğan önceliklerinin bir sembolü olmasındandır. Bu ihtiyaçlar 19. yüzyıl Avrupa’sını biçimlendiren politik milliyetçilik ve ekonomik emperyalizm akımlarından ve bunların yarattığı bazen monarşiyi besleyen, bazen tehlikeye sokan yeni düşünce ve yönetim sistemlerinden gelmektedir. Bu çalışma çeşmenin inşasının arkasındaki bütün bu politik, ekonomik ve sanatsal etkileri araştırarak çeşmeyi 19. yüzyıl Alman kültürü çerçevesinde tekrar anlamayı amaçlamaktadır. Dönemin politik ve ekonomik gerçekliği Alman İmparatorluğu odağa oturtularak açıklandıktan sonra bu dönemde Alman topraklarına hakim olan mimari akımlar ve Alman anıtları incelenmiş, Alman Çeşmesi bu veriler kapsamında ele alınmıştır. Osmanlı kültürünün bütün bu süreç içindeki yeri de böylece anlaşılmaya çalışılmıştır. Araştırmanın sonunda yaratılan çerçeve içinden bakıldığında çeşmenin Osmanlı toplumunun gündelik ihtiyaçlarından doğan bir eserden çok yabancı bir ülke içinde yapılmış, kolonyalist izler taşıyan bir Alman anıtı ve bu dönemde Alman topraklarında inşa edilen anıtlarda da görüldüğü gibi kişisel olarak II. Wilhelm’in bir eseri olduğu görülmektedir. Çeşmenin tasarımının temelinde yatan en önemli etki onu inşa eden hükümdardır ve tasarımın bütün kararları onun istek ve ihtiyaçları yönünde gerçekleşir. II. Wilhelm’in üslup ve biçim konusundaki kararları kişisel inanç ve hayallerinden doğmaktadır. Alman Çeşmesi’nin tasarımının temelini oluşturan baldaken strüktürü Kayzer’in kutsallık ve hanedanlık sembolü olduğuna inandığı bir plan tipidir. Neo-Bizans üslubu ise Bizans kültürünün Hristiyan tarihi içinde sahip olduğu, bu kültürün doğuşuna ve oluşumuna ev sahipliği etmiş xix olmasından gelen saf Hristiyan ruhunu biçimlendirişi ile onun tercih ettiği üsluplardandır. İki ülkenin hükümdarları arasındaki dostluğun çeşmenin yapımının gerekçesi olması dışında Osmanlı İmparatorluğu’nun çeşmenin yapımında etkisi yapılacağı yerin kararıyla sınırlıdır. Diğer bütün kararlarda Alman Kayzeri tekil olarak etkili olmuştur. Çeşmenin sadece içme suyu dağıtan dinlenme banklarına sahip bir şehir mobilyası olarak tasarımı Osmanlı kültürünün sınırlarının dışında biçimlenen, Avrupa kültürünün ihtiyaçlarına cevap veren bir eser olduğunu göstermektedir. Çeşmenin bu ihraç edilmişliği taşıdığı anlam ve kavramların Osmanlı hayatına tercüme edilememiş olmasından da anlaşılır. Alman halkı çeşmenin inşasından ülkeler ve halkları arasındaki dostluğun ilerlemesi gibi kazançlar umarken çeşme Osmanlı halkı tarafından ilgisizlikle karşılanmıştır. Yapının anıtsallığı ve bu anıtsallık kavramının Alman kültürü içinde karşılığı olan gündelik hayat ve özel günlerdeki aidiyeti Osmanlı hayatı içinde kendine yer bulamamıştır. Çeşme, iki kültürün karşı karşıya geldiği ve bir çatışma olmasa da aktif bir iletişimin de kurulamadığı bir diyalog olmuştur.

The German Fountain (Alman Çeşmesi) is an open fountain in the Sultanahmet Square in İstanbul. The design principles of its form and function distinguish this building from the other fountains of its time. It also makes it stand out in the square, which has many important architectural monuments from different eras of the history of İstanbul Sultanahmet Square was always an important centre in the city which was the capital of two great empires, Byzantine and Ottoman. In the Byzantine time this space was a hippodrome where games and races took place and the rulers and their people got a chance to interact. It was the space where petitions were delivered to the emperor and where the riots started. Situated between the imperial palace, imperial church and the main axis roads, it held the pulse of the everyday life in the city. In the Ottoman times it kept its place as a space for games and festivals even though the interactions between the people and the rulers had changed dramatically. Still, this was a space for the people to come together and for the rulers to communicate and control them through organizations ranging from birthdays, celebrations for religious holidays to events planned to intimidate foreign powers like festivals before and after wars. It was again close to the Topkapı, which was the residence of the Ottoman sultans until they decided to build palaces on the Bosporus. The square is surrounded with important monuments like government and religious buildings from Byzantine and Ottoman times and obelisk and columns, which remain as the traces of the hippodrome, and the monuments adorning its spina. The fountain is also situated on the axis determined by this spina with a small dislocation. With this location it achieves in appearing like a part of this organization, which was decided and realized 1500 before its own creation. The fountain was a gift of the German Kaiser Wilhelm II, hence its giving name by the Turkish people. The Kaiser visited Ottoman Empire three times during his reign and after his second trip in 1898, which was a particularly majestic one and ended successfully he decided to give a gift to the sultan and his people. The relationship between the German and Ottoman Empires at this time was a fruitful collaboration for both parties. They were working together in big and ambitious economical and political projects like Bagdad Railways. This project was not only going to help German merchants control very important trade routs and so help German Empire to get ahead in the competitive economical environment of the 19. century, it was also going to help Ottoman state to be able to reach to the eastern provinces of its domain easily and swiftly, be it to supply provisions or deploy military troupes. xxi This was not the only area in which these countries were working together. German Empire had become the protector of Ottoman Empire in the world politics. Not only was he a protection against Russia and his plans for the Bosporus, he was also supplying information about the revolutionary Turks in Europe trying to depose Abdülhamid II. and helping the Empire in its effort to reform itself. Ottoman Empire was in the process of a comprehensive reformation and German influence could be seen in every part of these reforms, especially in military and state affairs. It is clear to see that the relationship was very important for both parties and the rulers were showing this with their friendly interactions, correspondence and gifts. Their personal relationship had become the focal point of the relationship of their countries. Wilhelm II’s trips to İstanbul were one of the indicators of this policy. During his trips he and Sultan were acting like close friends who respect and care for each other and each others subjects. The sincerity of this act can be debated of course, it was in its essence politics after all, but even it was all just an act, it was obvious that they were both invested in it. So, it was not surprising when the Kaiser decided to give a fountain to the Sultan as a gift. The German authorities controlled every step of the construction of the fountain. The involvement of the Ottoman state was limited to the discussions about its placement and some preparation of this chosen site. The German court architect designed it according the sketches of the German Kaiser. Its parts were built in Germany and resembled in Istanbul by a German architect and German workers. The fountain itself as a cultural construct and the ideas behind it were completely German, which made it from the first point of conception a German monument. The decisions that shaped its design support this idea. Its design, generated from the baldachin structure and Neo-Byzantine forms has more in common with European culture than with Ottoman. The baldachin structure was commonly used in monumental structures in Germany. It was the basis for monuments and burial structures signifying honour and sacredness. This had its routes in the Christian religion and some of its holy structures and personage. Wilhelm II. was aware of this. He had even given a speech about the use of baldachin structure throughout ages for this purpose, to show nobility and holiness. The style chosen for it was Neo-Byzantine style, the revival of the Byzantine architecture in the 19. century Europe. This was the time period when the European architects and architecture theorists turned back to the past to find a style that would best suit to their time. Every part of the European history was discussed. This was also the case in Germany and the discussions were focused on the rivalry between Ancient Greek architecture to the architecture of the Middle Ages. Not only the architectural principles of these styles were discussed, but also the periods they were created. The culture and the religion of these periods were considered. Ancient Greek period was advocated because of its free individuals and democratic states, periods of Christian history because of this association. Another aspect of the discussion was the structural systems and after a while it became about architectures using round arches against the ones using pointed arches. The revivalist style, which preferred the round arch in the 19. century Germany was the Rundbogenstyl, literarily round arch style. It contained different styles of this type, like Neo-Byzantine, Romanesque and in some part Renaissance. The buildings in this style could be designed with the principles of one of these building periods or have traces of any number of them moulded together in a new fashion. The styles xxii Middle Ages always had a religious connotation. Gothic was seen as the true Christian style, for example. But a component of the Rundbogenstyl represented the birth of Christianity. In the Byzantine era Christianity had become a legitimate state religion and had grown stronger with the Byzantine Empire. Christian architecture was formed in this period. It had taken elements of the Roman architecture and reformed it to better serve its needs. It was part of two worlds Pagan Roman Empire and Christian Byzantine Empire. It was also born between east and west. It had a duality written in its routes, which made it preferable for people who wanted to be create Christian architecture at its purest and also a kind of architecture far away from what was common for the time. Byzantine architecture had one more appeal for the German architects. The German Empires in Middle Ages had strong connections with Byzantine Empire. Carolingians and Ottonians had learned Byzantine art of building and used it in their monumental structures. This created a cultural connection between the German culture of the 19. century and the one from the Middle Ages, which was a ideal for them as a united German nation. So, revival of the Byzantine art was the revival of the pure Christian and German forms alike. These ideas had an impact in the use of Byzantine style for the German Fountain. Wilhelm II’s fascination with Byzantine culture and German culture of the Middle Ages always affected his choice of the styles of buildings he commissioned. There was also one more important reason behind this. The history of the city the fountain was supposed to be built. Istanbul was Constantinople, the capital of the Byzantine Empire and home to its biggest and most famous monuments, like Agia Sophia. They were not only still important parts of the Ottoman capital, but were also a very influence on the Ottoman architecture itself. With the use of Byzantine style, the preferences of the German Kaiser, which were very much German was in agreement with the history of Istanbul and especially the square, the old hippodrome, it was going to be built on. The fountain was designed in the German ideals of monumentality. Its stately presence only added to this effect. Its inauguration ceremony was an example of this. It was a state ceremony, in which not only the ministers of the Ottoman Empire, but also a Special Mission from the German Empire and the armies of both nations took part. It was splendid and completely German yet again. German Fountain with all its characteristics is a German monument built in the Ottoman capital. This can also be seen in the expectations of the German public about the fountain. They expected it to affect the relationship between the nations favourably and they expected it to be treated with respect that they showed to their own monuments. But the fountain was built in a culture where monumentality in this sense had no place. Its given name as the Kaiser Wilhelm Fountain was forgotten almost immediately and in just one week damages started to appear on its mosaics and bronze parts were stolen. The reaction in the German papers showed their surprise on such acts. As the Ottoman public could not understand the meanings conveyed by the fountain, the German public was incapable to understand the neglect the fountain has received. Monuments as general depend on the ability of the people who will interact with them to understand their meanings and symbols. This was impossible for this monument with transported and untranslated meanings from the start.
A II. German Empire Project: from Kaiser Wilhelm Monument To German Fountain
Tez (Doktora) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2015
Thesis (PhD) -- İstanbul Technical University, Institute of Science and Technology, 2015
Keywords: Alman Çeşmesi Anıtlar 19. yüzyıl II. Wilhelm Neo-Bizans Mimarlığı; German Fountain Monuments 19th century II. Wilhelm Neo-Byzantine Architecture